2023
DOI: 10.1002/mco2.330
|View full text |Cite
|
Sign up to set email alerts
|

Novel aspect of neprilysin in kidney fibrosis via ACSL4‐mediated ferroptosis of tubular epithelial cells

Abstract: Although inhibition of neprilysin (NEP) might be a therapeutic strategy with the potential to improve the outcome of chronic kidney disease (CKD), the versatile function of NEP with its mechanism remains obscure in kidney fibrosis. In the study, we found that NEP was abnormally increased in tubular epithelial cells of CKD patients, as well as unilateral ureteral obstruction and adenine diet‐induced mice. Treatment with a United States Food and Drug Administration‐approved NEP inhibitor Sacubitrilat (LBQ657) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Neprilysin, or MME, is a membrane metallo‐endopeptidase and its expression is elevated in kidney biopsies of patients with chronic kidney disease, which is associated with kidney fibrosis. Inhibition of neprilysin can lead to reduced levels of inflammation related markers like TNF‐α, IL‐1β and IL‐6 (Lai et al., 2023). As mentioned before, ADH7 is reduced in aniridia limbal epithelial cells and contributes to retinol oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Neprilysin, or MME, is a membrane metallo‐endopeptidase and its expression is elevated in kidney biopsies of patients with chronic kidney disease, which is associated with kidney fibrosis. Inhibition of neprilysin can lead to reduced levels of inflammation related markers like TNF‐α, IL‐1β and IL‐6 (Lai et al., 2023). As mentioned before, ADH7 is reduced in aniridia limbal epithelial cells and contributes to retinol oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Specific inhibition of ACSL4 can significantly reduce lipid peroxidation and ferroptosis. [ 26 ] However, the ferroptosis inhibitor Ferrostain-1 (Fer-1) and vitamin E could only lower the lipid peroxide content, but not the expression of ACSL4. [ 27 , 28 ] These results suggested that ACSL4 catalyzes the initiation of lipid peroxidation and inhibition of ACSL4 could block ferroptosis from the source.…”
Section: Mechanisms Of Ferroptosismentioning
confidence: 99%
“…[ 48 ] Our studies confirmed that ACSL4-mediated ferroptosis was involved in UUO and adenine diet-induced kidney fibrosis. [ 6 , 26 ] Other reported signaling pathways include Smad3/ATF3/SLC7A11 signaling, [ 49 ] Akt/GSK-3p/Nrf2 signaling, [ 50 ] XBP1-Hrd1-Nrf2 signaling, [ 51 ] AKT/ mTOR/Nrf2 signaling, [ 52 ] TLR4/Nox4 signaling [ 53 ] and so on ( Figure 3A ).…”
Section: Kidney Fibrosismentioning
confidence: 99%